Evaluasi dan Perkuatan Struktur Pelat, dan Dinding Geser dengan Glass Fiber Reinforced Polymer (GFRP) - Turnip, Stephanus Martua; Alami, Fikri; Widyawati, Ratna (Universitas Lampung, 2019)
The Education hospital building of University of Lampung has been stalled and the construction is abandoned for years. So that, there is concern about the existing strength installed in the field. Therefore, it is necessary to evaluate and to strengthen the structure for increasing the strength and assuring appropriateness of the building. Two methods used in evaluating this building which weredirect survey method in the field and numerical method used the Finite Element Analysis (FEA) program. For strengthening calculations the American Concrete Institute code was applied (ACI 440.2R, 2008). The material for strengthening used Glass Fiber Reinforced Polymer (GFRP). The results showed that the existing concrete compressive strength on all structural elements decreased from the design which was 25 MPa. However, theexisting steel reinforcement tests showed good strength which greater than design strength of 400 Mpa.In strengthening calculation with GFRP type of SEH-51A which has tensility strength of 460 MPa, the material can increase flexural strength of several slabs that requiredfor strengthening. In addition, in the shear wall analysis, it concluded that the existing shear wall were strong enough to withstand the nominal shear forcesdesign that might be occured. Keywords : Structures Evaluation, Strengthening Structures, Glass Fiber Reinforced Polymers, Concrete Slab and Shear Walls.